Efektivitas Adsorpsi Logam Berat (Fe2+) Menggunakan Arang Aktif Batang Bambu (Bambusoideae) Teraktivasi NaOH - Al'farisi, Cory Dian; Irianty, Rozanna Sri; Damanik, Gery Andreas; Herman, Syamsu (Department of Chemical Engineering, Faculty of Engineering, UNRI, 2024)
The environmental pollution that was the center of attention was industrial wasted. Adsorption had been shown to been a more effective method for absorbing heavy metals from wastewater. Adsorption is the absorption of a substance on the surface of another substance. The adsorbent commonly used in adsorption is activated charcoal. Yellow bamboo is a material that could produced charcoal by carbonization. The research aimed to make adsorbents from bamboo, to characterize activated charcoal according to SNI 06-3730-1995. Bamboo stem activated charcoal capacity and calculated the effectiveness of charcoal adsorbents. Bamboo stems actively absorb iron ions (Fe2+). Variations in this process was particle sizes of 40+ 60-, 60+ 80- and 80+ 100- mesh and column diameter sizes of 2, 3 and 4 cm. The analysis results for the characteristics of the activated charcoal complied with SNI provisions, showing a moisture content of 4%, an ash content of 8%, and an iodine adsorption capacity of 1002.45 mg/g.. The best results in this research were the adsorption process at varying particle sizes of 80+ 100- mesh with a column diameter of 2 cm with an adsorption capacity value of 0.896 mg/g and an effectiveness of 90.48%. Variations in column diameter and particle size used affect the adsorption capacity and effectiveness of the adsorption process.